2019
DOI: 10.1111/pai.13041
|View full text |Cite
|
Sign up to set email alerts
|

Skin tests are important in children with β‐lactam hypersensitivity, but may be reduced in number

Abstract: Background There is no perfect agreement on how to perform an allergy workup in suspected beta‐lactam (BL)–allergic children, since skin test (ST)–induced pain is often a limitation. The aim of the study was to assess the possibility of reducing the number of ST in children when performing a complete allergy workup for BL hypersensitivity reactions. Methods A retrospective analysis of all patients referring to the Allergy Unit of the University Hospital of Montpellier (France) with positive responses in immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 22 publications
2
35
0
Order By: Relevance
“…84 However, in a retrospective study, STs have demonstrated a PPV of 99.4%, indicating their usefulness, before DPT. 85 Large multicentre studies, to evaluate the real diagnostic predictive values of ST, are needed. 86 In the case of NIR, due to the potential risk of triggering a severe reaction, the diagnostic procedure starts with a patch test and if negative, IDTs, although recent studies suggest the performance of IDTs with no need of a previous patch testing.…”
Section: In Vivo Testsmentioning
confidence: 99%
“…84 However, in a retrospective study, STs have demonstrated a PPV of 99.4%, indicating their usefulness, before DPT. 85 Large multicentre studies, to evaluate the real diagnostic predictive values of ST, are needed. 86 In the case of NIR, due to the potential risk of triggering a severe reaction, the diagnostic procedure starts with a patch test and if negative, IDTs, although recent studies suggest the performance of IDTs with no need of a previous patch testing.…”
Section: In Vivo Testsmentioning
confidence: 99%
“…In one retrospective review, patients with a nebulous history of penicillin allergy had rates of skin sensitization identical to that of patients without a penicillin allergy history (1.7%) [34]. Although a positive penicillin skin test result is often considered the reference standard for penicillin allergy, some patients may be sensitized (i.e., positive skin test result) but not clinically allergic, as shown by a negative oral penicillin challenge [35,36]. Standardized skin tests for cephalosporins are not available, although non-irritating concentrations for skin-testing have been published [37].…”
Section: Diagnostic Tests For Beta-lactam Allergymentioning
confidence: 99%
“…56 Finally, controversies exist about the reported safety and cost-effectiveness of direct DPT without previous STs for penicillin allergy delabeling in low-risk patients, [57][58][59][60] while others recommend to perform it with the culprit in all children with suspected BL hypersensitivity. 61 Importantly, the last position paper from the EAACI, in patients with BL allergy, recommends this procedure in children with mild maculopapular exanthema, although it is not recommended in adults experiencing low-risk NI-DHRs other than palmar exfoliative exanthema. 3 Further studies are necessary to provide data regarding the standardization of protocols for DPT, especially of those regarding NI-DHRs, for which there is currently no consensus.…”
Section: Drug Provocation Testmentioning
confidence: 99%